PENGARUH PENGENDALIAN INTERN, LOYALITAS DAN INTEGRITAS MANAJEMEN PADA PERILAKU ETIS KARYAWAN PT. ORINDO ALAM AYU DENPASAR - Dinajayanti, Ni Wyn Aryawati Dewi; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2016)
The intention from this research is for ana tomize the influence in internal control, loyalty and integrity in management on the ethical behavior of employees of PT. Orindo Alam Ayu Denpasar branch. The data usedin this study aresecondary and primary data . Methods of sampling using purposive sampling method . Data that meets the criteria as much as 40 samples . Technica lanalysis of the data used in th at research is multiple linear regression analysis . The result showed that internal control , loyalty and integrity of management influence on the ethical behavior of employees . This means that effective internal control , high loyalty and integrity of good management in the company may affect the ethical behavior of employees in a goverment .
Keywords: Internal control, loyalty, integrity and ethical behavior management